The eight-year long-term follow-up on the effectiveness of the quadrivalent human papillomavirus vaccine in Chinese women 20-45 years of age - Chao Zhao; Yun Zhao; Jingran Li; Mingzhu Li; Yanyan Su; Xin Mi; Su Yi La Tu; Danhua Shen; Lihua Ren; Yanyan Li; Linhong Wang; Lihui Wei (Taylor & Francis Group, 2022)
The quadrivalent human papillomavirus (4vHPV) vaccine has shown confirmative effectiveness in preventing HPV-related diseases among women and men around the globe. The phase III, randomized, double-blind efficacy study (Base study, NCT00834106) conducted in China showed 100% efficacy against HPV 16/18-related cervical intraepithelial neoplasia and efficacy against HPV persistent infection for 78 months. Participants aged 20-45 years who received three doses of 4vHPV vaccine or placebo during the base study were selected and invited for this long-term follow-up (LTFU) study to assess the long-term effectiveness of the 4vHPV vaccine in preventing HPV-related diseases. A total of 368 participants were included in this LTFU study with a median follow-up of 94 months. Among 27 participants (Vaccine vs. Placebo: 8 vs. 19) who underwent colposcopy and biopsy due to cervical cytological abnormalities or HPV infection, no HPV-16/18-related cases of cervical intraepithelial neoplasia (CIN), vulvar intraepithelial neoplasia (VIN), or vaginal intraepithelial neoplasia (VaIN) was observed in the vaccine group while two HPV-16-related cases (CIN1/VaIN) were observed in the placebo group. There were another two HPV-related cases (non-vaccine HPV types) found in the placebo group. Consistent with the findings from global studies that suggested long-term efficacy of 4vHPV vaccine, our study showed continued protective effect of 4vHPV vaccine against HPV-related precancerous diseases through a median follow-up time of 94 months with the longest follow-up time of 125 months after completing three doses of vaccination among Chinese women 20-45 years of age.